Effects of foreign trade on the economic performance of industries: Evidence from wood processing industry of Czechia and Slovakia - Andrea Sujová; Ľubica Simanová; Václav Kupčák; Jarmila Schmidtová; Adriana Lukáčiková (Economies, 2021)
As was first stressed by the classical economists Adam Smith and David Ricardo, international trade plays a crucial role in the growth process. The paper aims to analyze the influence of foreign trade on economic performance in the wood processing industry (WPI) of Czechia and Slovakia. The multivariate regression method (MLR), assumption tests for MLR models, and Granger causality test were applied to identify association between foreign trade economic performance, and indicators were formed to measure the effects of foreign trade at the industry level. The Granger test revealed the unidirectional causality in the Slovak WPI and bidirectional causality in the Czech WPI. The results revealed that the net export growth has a positive effect on the economic performance of the industry, but only if the growth in imports is lower than in exports. The balanced trade balance indicated no influence of foreign trade on economic performance. The paper contributes to existing knowledge with indicators for evaluation of foreign trade effects on the performance of the industry. The paper also brings new empirical knowledge in trade balance effects on the economic performance of industries.
Keywords: 330; contribution of foreign trade; economic performance; Granger causality; multivariate regression; net export; value added rate; wood processing industry